Experience quality in moderating lifestyle, brand awareness and taste quality on cleo consumer revisits - Dewi Sartikah; Surya Bintarti; Ilham Muhammad Mardiputra (Junal Ilmu Manajemen, 2023)
People must adopt a healthier lifestyle after the pandemic, one of which is by drinking mineral water regularly. In Indonesia, there are many brands of bottled drinking water, these five are the most well-known among the public, namely Aqua, Le Mineral, Ades, Cleo and Club. Cleo is bottled water that stands earlier than Le mineral, this is very interesting to analyze. This study aims to examine addiction between lifestyle, brand awareness, and taste quality on repurchase intention moderated by experience quality. The number of respondents in this study were 102 respondents who had purchased or consumed Cleo mineral water in the Bekasi Regency area. The taking of this population is non-probability sampling and the technique of taking respondents is purposive. This research was processed using a regression technique, which was processed using SmartPLS Software. This research proves 1) Customers who buy Cleo brand products feel that their lifestyle is in accordance with the Cleo brand product so that they have repurchase intentions. 2) The higher consumer awareness of the CLEO product brand, the higher the intention to repurchase again. 3) Cleo's products have high quality so that the quality of taste can affect repurchase intentions. 4) The quality of experience acts as a moderator predictor so it cannot moderate lifestyle on repurchase intention. 5) The quality of experience can moderate brand awareness on repurchase intentions. 6) Experience quality acts as a moderator predictor so it cannot moderate taste quality on repurchase intention.